Use of lactobacilli strains with probiotic potential in traditional fermented milk and their impact on quality and safety related to Listeria monocytogenes. (November 2019) - Papadopoulou, Olga S.; Argyri, Anthoula A.; Varzakis, Evangelos; Sidira, Marianthi; Kourkoutas, Yiannis; Galanis, Alex; Tassou, Chrysoula; Chorianopoulos, Nikos G.
Abstract: UHT bovine milk (low-fat) was inoculated with a starter culture and one adjunct strain, Lactobacillus plantarum 2035 or Lb. plantarum T571, with probiotic potential, and also with a cocktail mixture of three strains of Listeria monocytogenes at three different initial levels of inoculum and the milk was fermented to pH 4.5. Microbiological, physicochemical, molecular and sensory analyses were performed during storage at 4 and 12 °C. The probiotic samples displayed higher counts of lactic acid bacteria, higher acidity, lower pH and reduced counts of L. monocytogenes, in shorter time period than the control at 4 °C. Molecular analysis verified the presence of the probiotic strains until the end of storage at both temperatures and in adequate amounts; survival of L. monocytogenes strains depended on the treatment. Sensory evaluation showed that the probiotic fermented milks had desirable organoleptic characteristics, similar to the control.